Cartelization in gas markets. Studying the potential for a "Gas OPEC" - Steve A. Gabriel; Knut Einar Rosendahl; Ruud G. Egging; Hakob Avetisyan; Sauleh Siddiqui (Statistics Norway, Research Department, 2010)
Natural gas is increasingly important as a fuel for electric power generation as well as other uses due to its environmental advantage over other fossil fuels. Using the World Gas Model, a large-scale energy equilibrium system based on a complementarity formulation, this paper analyzes possible future gas cartels and their effects on gas markets in a number of regions across the world. In addition, scenarios related to lower transport costs and decreased unconventional gas supply in the United States are considered.
Keywords: Q41; D43; 330; natural gas; market equilibrium; complementarity model; energy